INOVASI PELAYANAN PUBLIK SEBAGAI UPAYA MEWUJUDKAN TRANSPORTASI BERKELANJUTAN DI KOTA BATAM - Ompusunggu, Melisa Fresa; Dompak, S.E., M.Si., Timbul (LPPM Universitas Putera Batam, 2023)
Batam City kept The quantity of vehicles in Batam City is expanding, various occupants who utilize theBatam trans transport mentioned that the Regional Government increment the armada so as not to standby excessively lengthy at the bus station and the transport appearance plan isn't not surprisingly. They wereconfounded that the transports on the Sekupang-Batam Center and Jodoh courses didn't come aroundthen. The exploration targets are to break down open help development as a work to acknowledgemaintainable transportation in Batam city and to examine the variables that frustrate public helpadvancement as a work to acknowledge practical transportation in Batam city. The hypotheses utilized inthis exploration are Public Assistance; Development Idea; Administration Advancement Idea; Public ServiceInnovation Indicators; Factors That Prevent Public Service Innovation furthermore, Feasible Transportation.the examination strategy utilized in this exploration is subjective with an illustrative methodology. Theconsequences of the examination on the job of the Batam City Transportation Organization in advancementin Batam City in offering Public Support Development administrations as a work to acknowledgeeconomical transportation in Batam City have been running great, however there should be moredevelopment